Zinc homeostasis and redox alterations in obesity - Franco, Cristina; Canzoniero, Lorella Maria Teresa (Frontiers in Endocrinology, 2024)
Impairment of both cellular zinc and redox homeostasis is a feature of several chronic diseases, including obesity.A significant two-way interaction exists between redox metabolism and the relatively redox-inert zinc ion. Redox metabolism critically influences zinc homeostasis and controls its cellular availability for various cellular functions by regulating zinc exchange from/to zinc-binding proteins. Zinc can regulate redox metabolism and exhibits multiple pro-antioxidant properties. On the other hand, even minor disturbances in zinc status and zinc homeostasis affect systemic and cellular redox homeostasis. At the cellular level, zinc homeostasis is regulated by a multi-layered machinery consisting of zinc-binding molecules, zinc sensors, and two selective families of zinc transporters, the Zinc Transporter (ZnT) and Zrt, Irt-like protein (ZIP). In the present review, we summarize the current state of knowledge on the role of the mutual interaction between zinc and redox homeostasis in physiology and pathophysiology, pointing to the role of zinc in the alterations responsible for redox stress in obesity. Since zinc transporters primarily control zinc homeostasis, we describe how changes in the expression and activity of these zinc-regulating proteins are associated with obesity.